Evaluasi Optimasi Mesin Tonase 650 Ton Injection Molding Menggunakan Metode Overall Equipment Effectiveness Studi Kasus PT. XYZ - Rivaldo, Andreyansen; Gusniar, Iwan Nugraha; Santosa, Aa; Sumarjo, Jojo (Patria Artha Technological Journal, 2021)
Increasing productivity is very important for companies to get success in their buisness processes.There is one example of increasing productivity is to increase production productivity in a company. PT. XYZ has 13 Tonnage Injection Molding machines that operate every day, three of 650 Ton tonnage machines are the oldest and often experience Down Time. Factors that affect the productivity of the 650 ton injection molding tonnage machine are Availability, Performance Rate, and Quality Rate. This study aims to determine the evaluation of optimization and maintenance repair of three 650 tonne tonnage machines. The method we used is to find the value of Overall Equipment Effectiveness, then analyze and breakdown the Down Time data and finally Fishbone analysis to find out the factors causing it. The result of this research is a data value of Overall Equipment Effectiveness for 10 days is 42.71% and the main focus of the factors causing Down Time is the machine factor and packaging loss. With the holding of this research, the researcher hopes to provide a detailed reference for PT. XYZ to make improvements or improvisations related to production productivity in the future.